Pengaruh Penggunaan Paylater terhadap Kesejahteraan Finansial Konsumen dalam Perspektif Hukum Ekonomi Syariah - Sativa, Adisty; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Paylater service has emerged as a significant innovation in the digital financial system in Indonesia, providing consumers with easy access to meet their daily needs. However, the rapid growth of this service raises challenges related to Islamic principles such as the avoidance of riba, gharar, and maysir. This study aims to explore how Islamic economic law can regulate Paylater services to remain compliant with sharia principles. By analyzing existing regulations, including DSN-MUI fatwas and OJK regulations, as well as the importance of transparency in contracts and financial literacy education for consumers, this study finds that the implementation of strict sharia-based regulations and increased consumer awareness can create an ethical and sustainable financial ecosystem. The findings of this research are expected to provide recommendations for service providers and relevant authorities in developing financial products that align with Islamic values.